Novel control strategy for three-stage 18-level hybrid multilevel inverter - Kadir, M.N.A.; Mekhilef, Saad; Ping, H.W. (IEEE, 2009)
This paper presents a multilevel multistage inverter design and its corresponding control strategy. The hybrid inverter has a high voltage stage composed of the six-switch conventional three phase inverter with its output connected in series with the outputs of three-level H-bridge medium and low voltage stages. The voltage ratio has been selected to enable both one state - approximation and PWM control modes effectively. The suggested control strategy has been developed to ensure minimum switching losses focusing on holding the higher voltage stage state as long as it is feasible. The reference voltage vector has been approximated to the nearest of the 919 vectors provided by the 18-level inverter. A special definition of state zone has been introduced for the low voltage stage to enable the achievement of the reference vector with minimum error. The proposed control strategy has been tested and its short computational time and low memory requirement has been proven.